Annual reviews of computational physics - Stauffer, Dietrich (World Scientific, 1997)
Includes bibliographical references p. 308 - 311; 7 articles: Fire spread in Natural fuel: Computational Aspects; direct Numerial simulation - A tool to study Turbulent Reacting; Molecular Dynamics simulations of Rayleigh - Taylor instability; quantum similation in Materials science: Molecular Monolayers; criticality in the Integer Quatum Hall Effect; Eloving Uniform and Non - uniform cellular Automata Networks; Modeling the Immune system: Architecture and Dynamics of Idiotypic Networks